Habilidades sociais, depressão, ansiedade e alcoolismo em bombeiros: um estudo correlacional - Oliveira, Paula Almeida de (2010)
Current researches have elucidated the importance of social skills for the quality of social relations, the well being and mental health of people. Even though mental disorders, regardless of diagnosis, have in common difficulties and losses of social relations, an appropriate social skills repertoire can be considered as a protective factor for depression, anxiety and use of alcohol. Seems relevant to investigate this association and associated factors, because the correlations between social skills deficits and mental disorders, although some disclosures in the literature, is still poorly understood. It is noteworthy also that the job of firefighter has peculiar characteristics that involve risk and compromise the quality of life of these professionals. Considering these aspects, this project aims to examine the relationship between social skills and depression, anxiety and alcoholism among firefighters. Considering these aspects, the present study aims to examine the relation between social skills and depression, anxiety and alcoholism in helping firemen for possible clarifications and understanding of this relationship. It can be defined as specific objectives: (1) To characterize social skills deficits and reserves in this population and also measure indicators for the disorders, (2) identify which classes of social skills deficit are related to mental disorders, (3) relate deficits and reserves of social skills and indicators of depression, anxiety and alcoholism, (4) evaluate possible factors that are related to the repertoire of social skills, for example, working time, gender, job, education, marital status and hierarchical distribution. The sample of this study are 303 military firefighters from a medium-sized city located within the state of Minas Gerais. Participants responded to instruments: Inventory of Social Skills (IHS-Del Prette-), the Beck Depression Inventory (BDI) and Anxiety (BAI) and Alcohol Use Disorders Identification Test (AUDIT). Data analysis was performed by SPSS statistical software version 15.0 and included descriptive and inferential statistics. It was performed Pearson correlations to examine the relationship between social skills of IHS-Del- Prette and their classes, and indicators of depression, anxiety and alcohol found in psychological tests. It was conducted ANOVA of repeated measures to evaluate intragroup differences between means of different classes of social skills. Considering the social skills repertoire, 22,8% of the firefighters are in need of social skills, while 60,7% amounted to a good and elaborate repertoire. With evidence of depressive symptoms were found 9,9% of firefighters and 8,9% with indicators of moderate to severe anxiety. 72,6% of participants were abstinent or low risk drinkers, other 6,6% reported abuse or dependence. The main findings indicate that social skills correlates significantly in the negative direction with depression (r =-,292, p =,000) and anxiety (r =-,277, p =,000), and not correlated with alcoholism (r =,008, p =,895). Among classes of social skills to obtain a result higher self-affirmation in the expression of positive affect (M = 70,42) and conversation and self-confidence (M = 62,10). The correlation of the first class was negative for depression (r =-,170, p = ,003) and anxiety (r =-,146, p = ,011) and second also being (r =-,277, p =,00) for depression and anxiety (r =-,280, p =,00). Although these correlations are weak, they still are revelant because they indicate a trend in the association between social skills and disorders that should be further investigated.